Legible pluralism: The politics of ethnic and religious identification in Malaysia - Graham K. Brown (University of Bath, Centre for Development Studies (CDS), 2009)
This paper examines the changing nature of ethnic and religious identification in Malaysia, drawing upon a survey of attitudes conducted in three locations in Malaysia. The paper argues that the widely perceived political shift from a prevailing ethnic Malay/non-Malay dichotomy towards a more religious Muslim/non-Muslim dichotomy is more complex that previous analyses have suggested. Moreover, the paper argues that while this shift has typically been seen as primarily societally driven, a more complete explanation of these changes needs to account for the changing role of the state in identity construction and boundary-making. To this end, the paper appropriates Scott's notion of 'legibility' and argues that the changing politics of ethnicity and religion in Malaysia must be located within the bureaucratic politics of identity and the increasing 'legibility' of religion vis-à-vis ethnicity for a state concerned to differentiate and stratify its citizenry.
Keywords: 330; ethnicity; religion; identity; Malaysia